2003
DOI: 10.1021/ja037577b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Metal Ion Transfer into Room-Temperature Ionic Liquids:  The Role of Anion Exchange

Abstract: The structure and stoichiometry of the lanthanide(III) (Ln) complexes with the ligand 2-thenoyltrifluoroacetone (Htta) formed in a biphasic aqueous room-temperature ionic liquid system have been studied by complementary physicochemical methods. Equilibrium thermodynamics, optical absorption and luminescence spectroscopies, high-energy X-ray scattering, EXAFS, and molecular dynamics simulations all support the formation of anionic Nd(tta)4(-) or Eu(tta)4(-) complexes with no water coordinated to the metal cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
265
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(289 citation statements)
references
References 76 publications
(75 reference statements)
11
265
0
Order By: Relevance
“…[7][8][9] Because ILs can also act as liquid ion exchangers, not only neutral but also charged complexes are extractable into the IL phase by ion exchange with the cationic or anionic constituent of the ILs. [10][11][12][13] Thus, the extractability and separability of metal ions in the IL extraction system are expected to differ from those of the usual organic solvent systems. 14,15 Recently, the present authors have reported on the synergistic ionic-liquid extraction of lanthanoids(III) (Ln(III)) with 2-thenoyltrifluoroacetone (Htta) as an acidic chelating extractant and several neutral ligands in 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([C4mim][Tf2N]).…”
mentioning
confidence: 99%
“…[7][8][9] Because ILs can also act as liquid ion exchangers, not only neutral but also charged complexes are extractable into the IL phase by ion exchange with the cationic or anionic constituent of the ILs. [10][11][12][13] Thus, the extractability and separability of metal ions in the IL extraction system are expected to differ from those of the usual organic solvent systems. 14,15 Recently, the present authors have reported on the synergistic ionic-liquid extraction of lanthanoids(III) (Ln(III)) with 2-thenoyltrifluoroacetone (Htta) as an acidic chelating extractant and several neutral ligands in 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([C4mim][Tf2N]).…”
mentioning
confidence: 99%
“…with 1-(2-thienyl)-4,4,4-trifluoro-1,3-butanedione (HTTA) as chelating agent, the mechanism was anion exchange rather than cation exchange [35]:…”
Section: Ion-exchange Mechanismmentioning
confidence: 99%
“…Many researchers have reported on the IL solvent extraction of metal cations, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and several reviews concerning the method have been published. [35][36][37][38] In the use of an IL as an extraction solvent, however, the recovery of the extracted metals is a serious problem because the IL phase cannot be evaporated.…”
Section: Introductionmentioning
confidence: 99%